GIS Combined with Multivariate Analysis in Supporting Digitalization Supply Chain Management of Halal Products: The Case Study of MSMEs in West Java Indonesia - Muslih, Muhamad; Gustian, Dudih; Somantri, .; Hasman, Deni (Engineering, Technology & Applied Science Research, 2025)
Micro, Small, and Medium Enterprises (MSMEs) struggle to compete in the global market, especially those producing halal products. Information system support is one solution that can solve the complex supply chain problem from producers to consumers. The objective of this study is to develop a Geographic Information System (GIS) supported by multivariate analysis for the digitalization of Supply Chain Management (SCM) of halal products in MSMEs located in West Java, Indonesia. Six attributes were evaluated: information technology, human resources, collaborative relationship, halal certificate, and SCM implementation as independent variables, and halal products as dependent. The results of the ANOVA test show that the six attributes are significantly different (p<5%). In addition, based on the Pearson correlation, only the collaborative relationship, human resources, and halal certificate attributes correlate more than 80%. The SCM analysis shows that supplier, manufacturing, and raw materials factors are the main levers in the halal product supply chain. A GIS-based information system was successfully developed, with satisfactory user acceptance results for usability, efficiency, reliability, and functionality. The results of this study indicate that this GIS-based system can help distribute halal products in MSMEs, especially those in the West Java area, Indonesia.